1994
DOI: 10.1128/iai.62.7.2754-2760.1994
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses of young mice to pneumococcal type 9V polysaccharide-tetanus toxoid conjugate

Abstract: Pneumococcal type 9V polysaccharide (PS), contained in the current pneumococcal vaccine, induces only a weak antibody response in young children and therefore is not an effective vaccine for young children. To increase its immunogenicity, a conjugate of PS to a protein carrier, tetanus toxoid (TT), was prepared. To quantify the immune response, mouse anti-9V PS immunoglobulin G (IgG) and IgM reference standards were established. Young mice immunized at 2 weeks of age produced IgM antibody in response to 9V PS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 41 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…its clinical relevance in vaccine research (47)(48)(49). Relative to nontransgenic (Ntg) siblings that express GH at normal levels (33, 50), MT-bGH20-tg mice grow to adult body weights that are significantly greater (51) and have significantly reduced life spans (25).…”
Section: Discussionmentioning
confidence: 99%
“…its clinical relevance in vaccine research (47)(48)(49). Relative to nontransgenic (Ntg) siblings that express GH at normal levels (33, 50), MT-bGH20-tg mice grow to adult body weights that are significantly greater (51) and have significantly reduced life spans (25).…”
Section: Discussionmentioning
confidence: 99%
“…The role of T cells in IgM responses to bacterial CPSs conjugated to proteins is controversial: some investigators have found substantially higher levels of CPS-specific IgM after CPS conjugation to carriers (8,37,63), while others have found minimal or no differences (10,56). It is interesting that in these studies, levels of CPS-specific IgM were substantially higher when high-molecular-weight CPSs isolated from pathogenic bacteria were used as test antigens (8,37,63), whereas minimal or no differences in hapten-or carbohydrate-specific IgM were observed when synthetic haptens or dextran was used (10,56). We found that immunization of T-cell-sufficient mice with high-molecular-weight GBSIII CPS conjugated to TT resulted in substantially higher levels of CPS-specific IgM than did immunization with unconjugated CPS (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Employing HSV amplicon technology my group vaccinated AD transgenic mice expressing mutated APP (Tg2576) with amplicons encoding either Ab 1‐42 (HSVAβ) or Ab 1‐42 fused with the molecular adjuvant tetanus toxin Fragment C (HSVAβ/TtxFC) (Bowers et al,2005). TtxFC was selected because it enhances immunogenicity and can skew an immune response toward a humoral T H 2 pathway (Lu et al,1994). The Tg2576 mice vaccinated with HSVAβ/TtxFC generated IgG1 antibodies consistent with T H 2 activation compared with HSVAβ vaccinated mice which initially expressed IgM antibodies followed by IgA isotypes (Bowers et al,2005).…”
Section: Immune Shaping For the Vaccination Of Admentioning
confidence: 99%